Financial, Food, and Housing Insecurity Due to Coronavirus Disease 2019 Among At-Risk People With Human Immunodeficiency Virus in a Nonurban Ryan White HIV/AIDS Program Clinic. (18th September 2020) - Sherbuk, Jacqueline E; Williams, Brooke; McManus, Kathleen A; Dillingham, Rebecca
Abstract: Coronavirus disease 2019 negatively impacts social determinants of health that contribute to disparities for people with human immunodeficiency virus (HIV). Insecurity of food, housing, and employment increased significantly in April 2020 among patients with lower incomes at a Ryan White HIV/AIDS program clinic in the Southern United States.